AB0360D ADHERENCE TO THERAPY IN RHEUMATIC PATIENTS TREATED WITH SUBCUTANEOUS BIOLOGICS. (June 2019) - Colaci, Michele; Puglisi, Tiziana; Calaciura, Elena
Abstract : Background: Patients' adherence to treatments is undoubtedly a fundamental part of a successful therapeutic strategy, even for rheumatic patients. In fact, the lack of adherence to treatment should be considered in all cases of "supposed" inefficacy of therapy prescribed. Objectives: We aimed to evaluate the adherence to treatment in a series of rheumatic patients from a single Centre (Catania, Sicily, Italy). Methods: We recruited 85 consecutive patients (M/F: 25/60; mean age 52.713.5 years) affected by chronic inflammatory arthropathies treated with subcutaneous biologics. All patients completed the 5-item version of Compliance Questionnaire for Rheumatology (CQR 5) 1 and the Morisky Medication Adherence Scales (MMAS-8) 2, in order to estimate their adherence to therapy. Moreover, all patients completed the Patient Global Assessment (PGA), the Visual Analogue Scale (VAS) for articular pain, and the Health Assessment Questionnaire (HAQ), in order to estimate their personal judgments on the effectiveness of therapies. Finally, the eventual presence of adverse events were reported. Results: Considering MMAS-8, 7/85 (8.2%) patients were low adherent to treatment (score <6), and 27/85 (31.8%) presented medium-grade adherence (score 6-7). Interestingly, the CQR 5 failed to precisely identify these patients. Adherence to therapy was not related to age, gender, education level, articular disease, adverse events, association with DMARDs. Notably, the use of etanercept (originator or biosimilar) was significant more frequent in low-adherent patients (5/7 vs. 19/78; p=0.017). Finally, a trend to higher mean levels of PGA (57.1 vs. 37.6; p=0.06), VAS (68.6 vs. 42.6; p=0.06), and HAQ (1.3 vs. 0.7; p=0.052) was reported in low-adherent patients. Conclusion: Our preliminary study confirmed that the low adherence to therapy (better identified with MMAS-8) is a relevant issue in the management of rheumatic patients treated with biologics. Moreover, low-adherent patients tend to perceive a worse disease condition. Further studies can clarify if low adherence is causally associated with less efficacy of therapy. References: [1] Hughes, et al. BMC Musculoskeletal Disorders 2013; 14:286. 2. Morisky DE, et al. J Clin Hypertens 2008; 10:348–354. Disclosure of Interests: None declared